The Implementation of Government Regulation Policy Number 19 of 2008 About Sub-District in Biak Numfor District, Papua Province - Amiruddin Amiruddin; Dahlan Dahlan; Yohanes Ayer (PINISI Discretion Review, 2021)
The elite cadre in society through the instruments of political parties and other social institutions seems to have stalled, even running without an adequate process. Therefore, this study aims to determine the implementation of Government Regulation Policy Number 19 of 2008 in Biak Numfor Regency and the inhibiting factors for the Implementation of Government Regulation Policy Number 19 of 2008 in Biak Numfor Regency. This study uses a descriptive research method with a qualitative approach. The reason for using a qualitative approach as a research approach is because researchers see the nature of the problem being studied can develop naturally according to the conditions and situations in the field. The results showed that the implementation of PP No. 19/2008 on sub-districts in Biak Numfor Regency, Papua Province, was seen from the aspect of communication, sources, dispositions/trends or behaviors, and the bureaucratic structure had not been running well and other factors The obstacles to the implementation of PP No. 19/2008 on sub-districts in Biak Numfor Regency are influenced by (a) The influence of external pressure, (b) The influence of personal characteristics, (c) The influence of outside groups; and (d) The influence of past circumstances.